1993
DOI: 10.2134/jnrlse.1993.0145
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Instruction for Introductory Genetics

Abstract: Computer-assisted instruction (CAI) offers a valuable supplemental teaching aid for courses that require repetitious drill to develop problem-solving skills. Computer assisted genetics instructor (CAGI) help students and teacher identify weaknesses and misconceptions, provides interactive drill to encourage students to master problem-solving, and reduces the need for continuing teacher tutorial time. CAGI contains multiple-choice questions developed by the course instructor and immediately acknowledges correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The body of research dealing with CAI in science classrooms and its impacts on students' science learning is abundant, yet with mixed results. Some research found that CAI was effective in improving students’ science achievement or their attitudes toward science (Chang, 2000[earth science]; Ferguson & Chapman, 1993[biology]; Hughes, 1974[physics]; Levine, 1994[general science]; Whiting, 1985[biology]; Yalcinalp et al, 1995[chemistry]). On the other hand, other researchers have found that traditional instruction was as good or better than CAI (Morrell, 1992[biology]; Olugbemiro, 1991[biology]; Summerlin & Gardner, 1973[chemistry]; Wainwright, 1989[chemistry]).…”
Section: Introductionmentioning
confidence: 99%
“…The body of research dealing with CAI in science classrooms and its impacts on students' science learning is abundant, yet with mixed results. Some research found that CAI was effective in improving students’ science achievement or their attitudes toward science (Chang, 2000[earth science]; Ferguson & Chapman, 1993[biology]; Hughes, 1974[physics]; Levine, 1994[general science]; Whiting, 1985[biology]; Yalcinalp et al, 1995[chemistry]). On the other hand, other researchers have found that traditional instruction was as good or better than CAI (Morrell, 1992[biology]; Olugbemiro, 1991[biology]; Summerlin & Gardner, 1973[chemistry]; Wainwright, 1989[chemistry]).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been published on the use of computers as teaching tools (Cassel and Elrick, 1992;Hannaway et al, 1992;Cross, 1993;Kohut et al, 1993;Robinson and Schafer, 1993;Fermanian and Wehner, 1995;Scott and Smith, 1995). Ferguson and Chapman (1993) reported that computer applications helped the students to improve their grades. Michaels (1993) argued that new technologies encourage students to approach the problem in a fresh way, as they may have developed a pattern for their approach to a term paper, laboratory report, or class presentation.…”
mentioning
confidence: 99%